La transizione ecologica come oggetto etnografico: posizionamento e intenzioni alla prova del campo (Sud Sardegna) - Elena Apostoli Cappello (Archivio Antropologico Mediterraneo)
Within an H2020 mandate framework, the research described here aims to understand the role of some local socio-cultural aspects in the ecological and particularly energy transition processes promoted by the European decarbonization agenda, in its local effects in the former mining region of Sulcis (South Sardinia). At the same time, this study intends to discuss the mandate and bring out different aspects of the ethnographic relationship that exceed the researcher's intentions, illustrating some of the different unexpected outcomes of her presence in the field by discussing the ethnographic positioning. Carloforte, the only town on the island of San Pietro, not far from the southwestern edge of Sardinia's Sulcitan coast and opposite the large industrial hub of Portovesme, is a site whose salient feature, geographically speaking, is marginality. However, it lies at the center of global, energy and geopolitical dynamics.